2016
DOI: 10.1182/blood-2016-01-694265
|View full text |Cite
|
Sign up to set email alerts
|

Moving treatment-free remission into mainstream clinical practice in CML

Abstract: The dramatic success of tyrosine kinase inhibitors (TKIs) has led to the widespread perception that chronic myeloid leukemia (CML) has become another chronic disease, where lifelong commitment to pharmacologic control is the paradigm. Recent trials demonstrate that some CML patients who have achieved stable deep molecular response can safely cease their therapy without relapsing (treatment free remission [TFR]). Furthermore, those who are unsuccessful in their cessation attempt can safely re-establish remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
263
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(278 citation statements)
references
References 47 publications
5
263
0
10
Order By: Relevance
“…Similarly, since 81% of patients in stable MR3 though not MR4 remain recurrence-free at 12 months, it is also clinically reasonable to offer de-escalation to such patients. It has been suggested that the absence of stable MR4 should be a 'red light' warning against treatment cessation 4 . The present report is confined to treatment de-escalation so does not allow comment on this, but does suggest that as long as the patient is in stable MMR, de-escalation may be a reasonable option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, since 81% of patients in stable MR3 though not MR4 remain recurrence-free at 12 months, it is also clinically reasonable to offer de-escalation to such patients. It has been suggested that the absence of stable MR4 should be a 'red light' warning against treatment cessation 4 . The present report is confined to treatment de-escalation so does not allow comment on this, but does suggest that as long as the patient is in stable MMR, de-escalation may be a reasonable option.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established that some patients with enduring deep molecular responses to TKI therapy can discontinue treatment (reviewed in 4,5 ). Early studies were confined to patients with undetectable BCR-ABL1 transcripts by standard reverse transcriptase polymerase chain reaction (RT-PCR), and defined molecular recurrence as the reappearance of BCR-ABL1 transcript positivity 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Achieving and maintaining DMR may give patients an opportunity to temporarily discontinue the TKI treatment (for example in female patients who want to get pregnant), and TFR was investigated in several studies, first with imatinib and then with 2GTKIs (nilotinib or dasatinib) [15]. In these studies, patients experienced many potential positive impacts of TFR, and relief of TKI-related AEs were the most frequently reported, although discontinuation of TKIs could be associated with a toxicity, so-called 'withdrawal syndrome,' presenting with musculoskeletal pain which starts, or worsens after 1-6 weeks from TKI discontinuation [16].…”
Section: Treatment-free Remission (Tfr) In Patients With CMLmentioning
confidence: 99%
“…Indeed, hematology has been at the heart of such fundamental work as the understanding of iron regulation in red blood cell mediated tissue oxygenation, 1 or the deciphering of the intricate molecular interactions between endothelial cells, platelets and plasmatic proteins in the early stages of hemostasis. 2 Deeper insights into cell biology have also been attained through the use of the easily available blood or bone marrow cells and cell lines derived from hematological malignancies. Moreover, the notion of the importance of the microenvironment of many cells has certainly found fertile ground in the study of the bone marrow or diseased lymph nodes involved in leukemia and myeloproliferative or lymphoproliferative disorders.…”
Section: Research In Morphology and Flow Cytometry Is At The Heart Ofmentioning
confidence: 99%
“…1 The goal is to define patients in whom treatment can be stopped safely and to establish a strategy for treatment discontinuation. 2 This is not the first amazing success in some 50 years of basic and clinical research underlying the success story of CML: the detection of oncogenes and of kinase activity in many of them was fortuitous, since it was a byproduct of the search for human leukemia viruses. In realization that most animal leukemias could be induced by viruses, this was a high priority research field in the late 1960s and early 1970s.…”
mentioning
confidence: 99%